The socio-economic impacts of energy policy reform through the lens of the power sector – Does cross-sectional dependence matter?. (August 2022) - Nepal, Rabindra; Phoumin, Han; Musibau, Hammed; Jamasb, Tooraj
Abstract: The reform of the power sector is one of the widely pursued energy policy in developing economies with core objectives around improving socio-economic outcomes. The empirical evidence, however, has not quantified the reform impacts separating the effects of common factors such as drivers of reforms among reforming countries. This is the first study in the reform literature to investigate the socio-economic impacts of power sector reforms accounting for cross-sectional dependence. We focus on the 18 non-OECD Asian economies, which includes member countries of important economic regions of the ASEAN and the SAARC for the period 1990–2018. The findings of our study suggests that power sector reforms have generated positive economic impacts and social welfare such as human development and income inequality. Electricity reforms have also contributed to reducing network energy losses and operational efficiency improvements. Our results are robust to alternative model specifications that consider interaction effects among power sector reforms. We conclude that power sector reform has been an enabler to achieve interrelated sustainable development goals such as achieving economic growth and reducing income inequality in developing economies. Highlights: This study quantifies the reform impacts accounting for cross-sectional dependence. Controlling the impacts of common factors facilitates context-based polices design. We investigate the reform impacts controlling for cross-sectional dependence. The socio-economic and technical impacts of reforms are mixed. Reforms will facilitate meeting the objective of the SGDs if implemented well.